The Effect of Snowball Throwing Learning Model on Student Learning Outcomes in Civic Education Subjects Class IV Elementary School - Fitri Oktavia Ningrum; Ja'far Sanusi (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
The purpose of this study was to determine the influence of the snowball throwing learning model on student learning outcomes in the civics class IV at Elementary School. The method that the researchers used was a quasi-experimental method with the design of the nonequivalent control group design. The data collection technique in this study used observation, interviews and tests, the test used was an enrichment sheet. With the data analysis techniques used in this study are validity test, reliability test, difficulty level test, question differentiator test, normality test, homogeneity test, and hypothesis test. Based on the hypothesis test in this study using the independent sample t test or what is known as the unpaired t test using post test data, namely the Sig. (2-tailed) value of 0.000 < 0.05, it can be interpreted that the Independent Sample T-Test can be said that the H0 is rejected, which means that there is an influence of the snowball throwing learning model on student learning outcomes in the subject of Ppkn grade IV at Elementary School.